NDC Analysis for Vietnam’s agriculture sector targets by 2030 - Vu Hong Trang; Bui Tan Yen; Nelson, Katherine; Tran Dai Nghia; Sander, Björn Ole (International Rice Research Institute, 2022)
Production of rice is essential to Vietnam’s economy but paddy rice production also contributes significantly to the nation’s greenhouse gas (GHG) emissions. Rice production emitted 45 million tons of carbon dioxide equivalent (MtCO2e) in 2010, equating to 18% of total national GHG emissions (Tran et al., 2019). A variety of options to reduce GHG emissions during the production of rice must be implemented to achieve Vietnam’s Nationally Determined Contribution (NDC) and green growth strategies. One of the most promising options is alternate wetting and drying (AWD), an irrigation technique in which fields are irrigated and then allowed to dry out to a certain point before irrigation commences. This technique can reduce methane emissions by as much as 50% on average without a reduction in yield (Carrijo et al. 2017). We provide multiple project scenarios (MARD, 2016; Mai & Ngo, 2020; and Tran et al., 2019) to achieve this target under differing technology adoption baselines and with low to high infrastructure investment prospects.